Manajemen Adaptif Program Pendidikan Kesetaraan Paket C untuk Pengembangan Sumber Daya Manusia Peserta Didik: Studi Kasus di PKBM Budi Utama Surabaya - Ainiah, Ulfatin; Nugroho, Rivo (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: The Package C equivalency education program provides an alternative pathway to upper-secondary education for learners who are not fully served by formal schooling. This study examines how program management at PKBM Budi Utama Surabaya supports learners’ human resource development through academic learning, flexible delivery, and life-skills activities. A qualitative case-study design was employed. Data sources were selected purposively and comprised the PKBM manager, a Package C biology tutor, learner observation, and institutional documentation. Data were collected through in-depth interviews, classroom observation, and document review, then analyzed through data reduction, data display, conclusion drawing, and verification. Source and technique triangulation were used to strengthen credibility. The findings indicate that program management is organized through planning, organizing, implementation, and evaluation. Its distinctive feature is adaptive delivery: face-to-face learning is complemented by online communication and substitute assignments for learners whose work schedules constrain attendance. Human resource development is pursued through the integration of academic learning with barista, archery, river exploration, Qur’anic learning, and entrepreneurship activities. These practices support the development of knowledge, vocational exposure, independence, responsibility, and readiness for further study or work. However, unstable attendance, shift work, limited learning time, weather constraints, and incomplete assignments remain important barriers. The study concludes that Package C management can function as a human resource development strategy when institutional management combines program standards with flexible, contextual, and learner-responsive services. The findings are analytically transferable to similar community learning centers, but the single-site design and limited data sources require cautious generalization. Abstrak: Program Pendidikan Kesetaraan Paket C merupakan jalur alternatif pendidikan setara sekolah menengah atas bagi warga belajar yang belum terlayani secara optimal oleh pendidikan formal. Penelitian ini menganalisis bagaimana manajemen program di PKBM Budi Utama Surabaya mendukung pengembangan sumber daya manusia peserta didik melalui pembelajaran akademik, layanan yang fleksibel, dan kegiatan kecakapan hidup. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Sumber data dipilih secara purposif, meliputi pengelola PKBM, satu tutor Biologi Paket C, observasi peserta didik, dan dokumentasi lembaga. Data diperoleh melalui wawancara mendalam, observasi pembelajaran, dan telaah dokumentasi, kemudian dianalisis melalui reduksi data, penyajian data, penarikan kesimpulan, dan verifikasi. Kredibilitas data diperkuat melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa pengelolaan program berlangsung melalui perencanaan, pengorganisasian, pelaksanaan, dan evaluasi. Ciri pentingnya adalah layanan adaptif berupa kombinasi pembelajaran tatap muka, komunikasi daring, dan tugas pengganti bagi peserta didik yang terkendala jadwal kerja. Pengembangan sumber daya manusia dilakukan dengan mengintegrasikan pembelajaran akademik dengan kegiatan barista, panahan, susur sungai, mengaji, dan kewirausahaan sehingga mendukung pengetahuan, keterampilan vokasional, kemandirian, tanggung jawab, serta kesiapan melanjutkan pendidikan atau bekerja. Hambatan utama meliputi kehadiran yang tidak stabil, kerja shift, keterbatasan waktu belajar, cuaca, dan penyelesaian tugas yang belum optimal. Penelitian menyimpulkan bahwa manajemen Paket C dapat berfungsi sebagai strategi pengembangan sumber daya manusia apabila standar program dipadukan dengan layanan yang fleksibel, kontekstual, dan responsif terhadap kebutuhan peserta didik.